Interaction Adolescent–Parent and Peer, Social Media,and Social Skill - Alfi; Krisnatuti, Diah; -Defina, Defina (Journal of Family Sciences, 2024)
Social skills are abilities that adolescents need to possess to form an attitude of empathy and social awareness. Adolescents acquire these social skills through good inter-family interactions at home. This study aimed to analyze the interaction between adolescents, parents, and peers, as well as the use of social media on social skills. This study involved 100 late adolescents aged 18–21 years throughout Indonesia. This study used a cross-sectional design and a survey method with a questionnaire tool using a Google form distributed during April 2022. The study results showed that the quality of adolescent-parent and peer interactions, use of social media, and social skills were moderate. The correlation test results showed a positive relationship between adolescent-parent and peer interactions and the use of social media with social skills. The regression test results showed a positive effect of adolescent-peer interaction and the use of social media on social skills. The conclusion was that the better the quality of adolescent interactions with peers and the use of social media, the greater the improvement in social skills. This research implies that a community that involves youth in social activities through Karang Taruna can provide youth with the opportunity to hone their social skills.